2010
DOI: 10.1021/jo100053j
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of (+)-Estrone Exploiting a Hydrogen Bond-Promoted Diels−Alder Reaction

Abstract: Starting from Dane’s diene and methylcyclopentenedione, (+)-estrone is synthesized along the Quinkert−Dane route in 24% total yield. The key step is an enantioselective Diels−Alder reaction promoted by an amidinium catalyst as efficiently as by a traditional Ti-TADDOLate Lewis acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 48 publications
0
27
0
2
Order By: Relevance
“…The product in each case ( C11 or C12 ) was suggested by a molecular ion peak upon ESI-MS analysis, but the trace quantity thwarted isolation. Alternatively, attachment of 1,3-dimethoxy-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)benzene [59,60] (derived here from 2,6-dimethoxyphenyl boronic acid and pinacol) to the 15-position of the chlorin was investigated but found non-advantageous versus incorporation of the 2,6-dimethoxyaryl unit via the dipyrromethane in the Eastern half synthesis. The failure to incorporate the snap-on motif prompted return to an established route wherein the facially encumbering diphosphonate group is installed via the use of the Eastern half.…”
Section: Resultsmentioning
confidence: 99%
“…The product in each case ( C11 or C12 ) was suggested by a molecular ion peak upon ESI-MS analysis, but the trace quantity thwarted isolation. Alternatively, attachment of 1,3-dimethoxy-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)benzene [59,60] (derived here from 2,6-dimethoxyphenyl boronic acid and pinacol) to the 15-position of the chlorin was investigated but found non-advantageous versus incorporation of the 2,6-dimethoxyaryl unit via the dipyrromethane in the Eastern half synthesis. The failure to incorporate the snap-on motif prompted return to an established route wherein the facially encumbering diphosphonate group is installed via the use of the Eastern half.…”
Section: Resultsmentioning
confidence: 99%
“…Last but not least, mention should also be made of syntheses of steroids accomplished by use of classical organic methodology. Typical examples include the syntheses of (+)-or (Ϯ)-estrone reported by Corey et al, [6][7][8] Pattenden et al, [9] Mukai et al, [10] Göbel et al, [11] and Li et al, [12] or the syntheses of ent-desmosterol, [13] ent-cholesterol, [14,15] and ent-estradiol [16] by Covey et al and by Rychnowski et al…”
Section: Introductionmentioning
confidence: 99%
“…[8] Later Quinkert et al showed that the Diels-Alder reaction could be promoted by the application of a Lewis acid catalyst. [10][11][12][13] Organocatalysis has opened a new dimension in asymmetric catalysis in the last decade. [10][11][12][13] Organocatalysis has opened a new dimension in asymmetric catalysis in the last decade.…”
mentioning
confidence: 99%
“…EWG = electronwithdrawing group. [8][9][10][11][12][13] Our novel approach is based on the condensation of an aminocatalyst with an enal or 2,4-dienal to form either a dienamine or trienamine, respectively, which consist of a diene moiety attached to an activating and stereoinducing molecular handle. [20] A more recent development is the application of organocatalysis in targetoriented synthesis.…”
mentioning
confidence: 99%